2017
DOI: 10.17265/1934-8975/2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement on the Performance of Refrigeration System Using the Nano-Refrigerant

Abstract: Abstract:The purpose of the present experimental work is to investigate the performance (1 ton) refrigeration system using nano-refrigerant. Nano-refrigerant is alumina (ɣ-Al 2 O 3 ) nanopartcal with size (20-30) nm is dispersed into R-134a with volume fraction 0.01% and 0.02%. The experimental test rig consists of horizontal double tube counter flow heat exchanger fabricated of copper. The nano-refrigerant is evaporated inside the inner tube because of the heat gain from hot water passing in the annulus surro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(2 citation statements)
references
References 6 publications
(4 reference statements)
0
1
0
Order By: Relevance
“…Using SWCNT/R134a nanorefrigerant, [37] observed the viscosity of the nanorefrigerant increases as the concentration increased. [64] reported that the viscosity of Al2O3/R134a nanorefrigerant of nanoparticle size 20 -30 nm with a volume concentration of 0.01% and 0.02% increased as the concentration increased. An increase of 1.4% and 5.2% was obtained for 0.01% and 0.02% particle concentration respectively.…”
Section: ) Materials and Technologies For Sustainabilitymentioning
confidence: 99%
“…Using SWCNT/R134a nanorefrigerant, [37] observed the viscosity of the nanorefrigerant increases as the concentration increased. [64] reported that the viscosity of Al2O3/R134a nanorefrigerant of nanoparticle size 20 -30 nm with a volume concentration of 0.01% and 0.02% increased as the concentration increased. An increase of 1.4% and 5.2% was obtained for 0.01% and 0.02% particle concentration respectively.…”
Section: ) Materials and Technologies For Sustainabilitymentioning
confidence: 99%
“…The refrigerating effect is elevated because the thermal properties of Ag-doped nano-CuO are better than pure nano-CuO. Also, the overall conductivity of the refrigerant is also increased due to the nano-transitional elements mixed with it [22,23].…”
Section: Refrigerating Effectmentioning
confidence: 99%